Towards PubMed 2.0 - Nicolas Fiorini; David J Lipman; Zhiyong Lu (eLife, 2017)
Staff from the National Center for Biotechnology Information in the US describe recent improvements to the PubMed search engine and outline plans for the future, including a new experimental site called PubMed Labs.